Contributions to the Morphology of Plectrohyla mykter (Anura: Hylidae), with Comments on Some Controversial Characters and the Diagnosis of this Species (2015)
We describe the tadpole, juveniles, and two adult specimens of Plectrohyla mykter. The tadpole of this species is unique among Plectrohyla by having labial tooth row formula 4(4)/6. We found that tarsal fold, thoracic fold, and rostral keel are present in P. mykter but not evident in adults, and that the skin thickness is intermediate in comparison to other species of Plectrohyla. We conclude that these characters are not useful for the diagnosis of P. mykter and propose a new diagnosis for this species.